2018
DOI: 10.1253/circj.cj-16-1279
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Right Ventricular Ejection Delay in Brugada Syndrome Depends on the Type of <i>SCN5A</i> Variant ― Electromechanical Coupling Through Tissue Velocity Imaging as a Bridge Between Genotyping and Phenotyping ―

Abstract: Using the simple, non-invasive echocardiographic parameter RVED revealed a more pronounced 'electromechanical' delay in BrS patients carrying T variants ofSCN5A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In population controls (gnomADv3.1.2), both the TTN and SCN5a variants have not been detected so far. However, the SCN5a variant has been described in Clinvar (NM_000335.5(SCN5A):c.1003T>C, p.Cys335Arg) in a patient with Brugada Syndrome and in one family with atrial fibrillation [ 10 , 11 ]. The SCN5a variant is a point mutation (1003T>C) that alters the amino acid at codon 335 from the cysteine (C) to arginine (R) located in the first transmembrane domain ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In population controls (gnomADv3.1.2), both the TTN and SCN5a variants have not been detected so far. However, the SCN5a variant has been described in Clinvar (NM_000335.5(SCN5A):c.1003T>C, p.Cys335Arg) in a patient with Brugada Syndrome and in one family with atrial fibrillation [ 10 , 11 ]. The SCN5a variant is a point mutation (1003T>C) that alters the amino acid at codon 335 from the cysteine (C) to arginine (R) located in the first transmembrane domain ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…While gain of function mutations lead to an increase of INa and thus longQT syndrome, loss of function mutations cause conduction disease, Brugada syndrome, or DCM [ 17 , 18 , 19 ]. SCN5a p.C335R was reported previously in association with arrhythmia; however, its pathogenicity was not well investigated [ 10 , 11 , 20 ]. In this study, we identified the SCN5a p.C335R variant in a very large family with DCM and conduction disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies compared the echocardiographic characteristics of patients with BrS and healthy individuals. On one hand, there are studies that support the absence of structural alterations in patients with BrS [ 12 ]. On the other hand, it was found that BrS patients showed an increase in right ventricular size, especially in the outflow tract diameter (RVOT) and telediastolic (RVED) and telesystolic (RVES) volumes with statistically significant impact [ 12 , 13 , 14 ].…”
Section: Cardiac Imaging In Brs Patientsmentioning
confidence: 99%
“…On one hand, there are studies that support the absence of structural alterations in patients with BrS [ 12 ]. On the other hand, it was found that BrS patients showed an increase in right ventricular size, especially in the outflow tract diameter (RVOT) and telediastolic (RVED) and telesystolic (RVES) volumes with statistically significant impact [ 12 , 13 , 14 ]. In order to exclude overlap syndromes between BrS and cardiomyopathies such as arrhythmogenic right ventricular cardiomyopathy (ARVC), some studies analyzed BrS and ARVC patients.…”
Section: Cardiac Imaging In Brs Patientsmentioning
confidence: 99%